Plant growth promotion activity of Keratinolytic fungi growing on a recalcitrant waste known as "hair waste" - Cavello, Ivana Alejandra (2015)
Purpureocillium lilacinum (Thom) Samsom is one of the most studied fungi in the control of plant parasitic nematodes. However, there is not specific information on its ability to inhibit some pathogenic bacteria, fungi, or yeast. This work reports the production of several antifungal hydrolytic enzymes by a strain of P. lilacinum when it is grown in a medium containing hair waste. The growth of several plant-pathogenic fungi, Alternaria alternata, Aspergillus niger, and Fusarium culmorum, was considerably affected by the presence of P. lilacinum’s supernatant. Besides antifungal activity, P. lilacinum demonstrates the capability to produce indoleacetic acid and ammonia during time cultivation on hair waste medium. Plant growth-promoting activity by cell-free supernatant was evidenced through the increase of the percentage of tomato seed germination from 71 to 85% after 48 hours. A 21-day plant growth assay using tomato plants indicates that crude supernatant promotes the growth of the plants similar to a reference fertilizer ( > 0.05). These results suggest that both strain and the supernatant may have potential to be considered as a potent biocontrol agent with multiple plant growth-promoting properties. To our knowledge, this is the first report on the antifungal, IAA production and tomato growth enhancing compounds produced by P. lilacinum LPSC #876.